2013
DOI: 10.2741/4116
|View full text |Cite
|
Sign up to set email alerts
|

WNT3A modulates chondrogenesis via canonical and non-canonical Wnt pathways in MSCs 

Abstract: The multilineage commitment of mesenchymal stem cells (MSCs) is controlled via unknown mechanisms. In this study, we investigated the regulation of the differentiation of MSCs into chondrocytes via the Wnt signaling pathway. Overexpression of WNT3A in MSCs activated both the canonical and non-canonical Wnt pathways, which were responsible for different WNT3A-induced outcomes. WNT3A promoted MSC proliferation via the ß-catenin-mediated canonical Wnt pathway, and inhibited chondrogenesis of MSCs via the calcium/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Interestingly, we found SerpinE1, thrombospondin-1, IGFBP3, endoglin, and angiogenin to be abundantly secreted in fetal MSCs and iMSCs. The described role of SerpinE1, thrombospondin-1, and endoglin in wound healing [7880] indicate a putative fetal-like feature of wound healing properties of iMSCs in vivo [81, 82]. Our analyses revealed that aMSCs compared to fMSCs and iMSC secrete a reduced repertoire of cytokines and at significantly lower levels.…”
Section: Discussionmentioning
confidence: 65%
“…Interestingly, we found SerpinE1, thrombospondin-1, IGFBP3, endoglin, and angiogenin to be abundantly secreted in fetal MSCs and iMSCs. The described role of SerpinE1, thrombospondin-1, and endoglin in wound healing [7880] indicate a putative fetal-like feature of wound healing properties of iMSCs in vivo [81, 82]. Our analyses revealed that aMSCs compared to fMSCs and iMSC secrete a reduced repertoire of cytokines and at significantly lower levels.…”
Section: Discussionmentioning
confidence: 65%
“…However, comparison of RNA transcripts between WT and TFF2 −/− Mφ that were both exposed to damaged MTEC revealed that C amkk2b expression was significantly (>2-fold) under-represented in TFF2 −/− Mφ (Supplementary Figure 5b). Because C amkk2b is implicated in the calcium dependent pathway for Wnt glycoprotein expression 34, 35 , which in turn regulates multiple aspects of epithelial cell biology, we reasoned that Mφ-derived TFF2 may promote epithelial repair, at least partially, via regulating Wnt expression.…”
Section: Resultsmentioning
confidence: 99%
“…Using phosphospecific antibodies, we observed that Ser33/37/Thr41-phospho β-catenin (inactive) is totally absent in MSC cell lysate, thus suggesting that the Wnt/β-catenin is fully active in MSCs (Takam Kamga et al, 2016b;Wang et al, 2019). The requirement of a functional β-catenin-independent Wnt signaling, such as Wnt/Ca 2+ , Wn/Jnk, Wnt/Ryk, Wnt/Ror2, was also described in MSCs (Qiu et al, 2011;Qu et al, 2013;Jeong et al, 2020). Overall, the activation of the pathway plays a critical role in cell fate decisions, notably for MSC proliferation, self-renewal and differentiation.…”
Section: The Wnt Signaling In Mscsmentioning
confidence: 68%
“…One key mechanism of the suppressive role of Wnt/β-catenin on adipogenesis is the reduced expression of adipogenic transcription factors CCAAT/enhancer binding protein alpha (C/EBPalpha) and peroxisome proliferator-activated receptor gamma (PPARgamma) (Ross et al, 2000;Yuan et al, 2016). However, the use of Wnt/β-catenin inhibitors, such as Quercitin, reduce MSC proliferation and multipotency by favoring their osteogenic commitment and inhibiting both the chondrogenic and the adipogenic differentiation (Qu et al, 2013;Narcisi et al, 2015;Jothimani et al, 2020;Volleman et al, 2020). This model failed to explain the positive contribution of canonical Wnt in bone homeostasis in vivo (Wagner et al, 2020).…”
Section: The Wnt Signaling In Mscsmentioning
confidence: 99%